Rancangan Pembangkit Listrik Tenaga Mikro Hidro Di Kampung Dongi Kecamatan Nuha - Muhammad Naim; Ichsan Ristiawan (Dinamika : Jurnal Ilmiah Teknik Mesin, 2018)
One solution to solve electrical problems in the Dongi village of Nuha District is the provision of new and renewable energi sources that are environmentally friendly as an alternative to electricity supply. Source of new energi and renewable environmentally friendly in question is Hydro Micro Power Plant. The purpose of this research is to design a PLTMH in Dongi village, Nuha sub-district, East Luwu regency, so that it can solve the electricity problem in this area. The results showed that the components of PLTMH support in Dongi village were dam with dump type with concrete layer, take-up building with debit 12,00 m3 /second and door width of intake 2 unit, Trapezoidal carrier channel from stone pair plastered with discharge of 11.00 m3 /sec and equipped with drainage channels and control boxes and culverts, tranquilizers with construction of pairs of stone plastered with a basin base of corrosion concrete (without reinforcement) waterproof, fast pipe which will be mounted from PVC pipe type with diameter 3 inchi with total length 30 meter, Power House, drainage with bottom width 2 x 4.0 m, water height 1.0 m, and length 15 m, Turbine Cross-flow with turbine specification Age wear; at least 10 years, Reliability; 300 hours per year, Overhaul; 3 years, bearing, water seal, belt, Efficiency at least 55%, Casing does not leak, Asynchronous Generator with type specification: Induction Motor As Generator, horizontal axle, foot mounted, TECO or equivalent, Double Bearing, power rating: 40 hp, 30 kW, 3 phase, 50 Hz, 220/380 V, operational rating: continous duty, warranty efficiency: 87%, 4 pole pairs, Control system uses load settings so that the amount of power generator output is always equal to load, and Power distribution network is designed using NYY wire with pole in the form of wooden pole. Keywords: Micro hydro, Weir, Turbine, Asynchronous generator